Three-phase coupled modelling research on rain–wind induced vibration of stay cable based on lubrication theory. (May 2016) - Wang, J.; Lu, P.; Bi, J.H.; Guan, J.; Qiao, H.Y.
Abstract: Cables of cable-stayed bridges may vibrate with large amplitude under wind and rain, which is known as rain–wind induced vibration (RWIV). According to the pervious researches, the formations and oscillations of rivulets on stay cable surface play important roles in RWIV. In this paper, four different 2D models are presented based on lubrication theory, and the best way of simulating RWIV through lubrication theory is confirmed by the comparisons of rivulet motions and cable vibration responses between these four models and pervious researches. On this basis, the relations among rivulet motions, cable aerodynamic forces and vibration responses are investigated to reveal the mechanism of RWIV. Numerical simulation results show that when RWIV occurs, the periodic oscillations of rivulets around cable lead to the periodic fluctuations of cable lift and drag, whose frequencies are almost equal and close to cable natural frequency. Under the periodically fluctuant lift and drag, cable vibrates with large amplitude in across-wind and along-wind directions, which may further enhance the circumferential oscillations of rivulets conversely. These confirm the conclusion that the resonance between rivulets and cable oscillation may be one of the main reasons for RWIV. Graphical abstract: Highlights: Coupled equations of water film evolution and cable vibrations are presented. The effects of along-wind vibration of RWIV are discussed. The best way of simulating RWIV by Lubrication theory is presented. The relations among rivulets, aerodynamic forces and cable vibrations are analysed. The resonance between rivulets and cable is the main reason for RWIV.